Investigation of machinability in the milling process of carbon fiber-reinforced thermoplastic and thermoset matrix composites - Callisaya, Emanuele Schneider [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Carbon fiber-reinforced polymers (CFRPs) are widely employed in automotive and aerospace applications due to their high strength-to-weight ratio. Although typically produced near net shape, machining is required to meet final dimensional accuracy and surface quality demands. However, their anisotropic, heterogeneous structure and the abrasiveness of carbon fibers often lead to critical surface and subsurface damage, making the machining of composites a challenge. This work investigates the machining by the milling of thermoplastic matrix composite (Toray Cetex® TC910PA6) and the thermoset matrix composite (Toray E732®) using four cutting tool geometries: two helical (i.e. the diamond-coated Neutral Helix (NH) and Lefthand helix (LH)) and two multi-edge (i.e. with Zr coating (ME-ZR) and with diamond coating DURA® (ME-D)). Milling tests were conducted varying the feed per tooth “fz” (0.025; 0.050; 0.075 and 0.10 mm/t) and rotation “n” (4000 and 8000 rpm). Machinability was assessed through surface quality analysis, delamination occurrence and monitoring of cutting parameters influence on the power consumption, vibration of the system, acoustic emission and the wear of cutting tools. Statistical analyses of variance (ANOVA), analysis of means (ANOM), Signalto-Noise analysis (S/N) and comparative and normality tests, as well optimization with the Response Surface Methodology (RSM) were applied evaluate parameter effects. Furthermore, static tests (i.e., tensile and static bending) and dynamic tests (i.e. axial fatigue) examined the influence of machining on mechanical performance. The thermoset composite presented increased resistance to cutting, with direct impact of the feed per tooth factor fz that led to elevated incidence of discontinuous fiber rupture during machining that favored delamination type II when using higher feed per tooth values (0.075 and 0.10 mm/t). Additionally, several regions of porosity were observed and discontinuous distribution of fibers that led to increased roughness of 2.2 µm. The results revealed that reducing the feed can act as a mitigating factor to fiber pullout phenomena, providing a reduction in delamination. The thermoplastic composite presented fewer transient vibrational peaks, as well as lower power consumption during machining. The most influential parameter for the milling process was the fz, resulting in surface finish improvement achieved with the application of 0.025 mm/tooth. Enhanced surface quality and reduction of lateral delamination was observed with the application of the Left-Hand helix tool (LH), with resulting Ra of 1.3 µm. The amplitude of power consumption was critically dependent on the change of cutting tool geometry, the multi-edge (ME-D) tool led to power consumption amplitudes that reached 4 times the average value of the helical cutting tools. The chips generated during machining presented drastically form change with the composite matrix variation due to different chip mechanism formation. Cutting tool geometry also affected chip formation in CFRP machining, the LH tool promoted best chip flow and superior surface finish, making them ideal for finishing machining. It was proven that the milling machining process did not reduce the static mechanical properties. However, significant impact in dynamic properties was confirmed to the condition fz = 0.02 mm/t and n = 4000 rpm, where the machining resulted in delamination, reducing fatigue life for high stress levels (75 to 85%).

Polímeros reforçados com fibras de carbono (CFRPs) são amplamente aplicados na indústria automotiva e aeronáutica devido a combinação de propriedades de resistência mecânica com a redução de peso de componentes. Embora geralmente produzidos em formato próximo ao final, componentes compósitos precisam ser usinados para atender aos requisitos de precisão dimensional e qualidade superficial. No entanto, devido à sua estrutura anisotrópica e heterogênea e a natureza altamente abrasiva das fibras de carbono, diversos danos críticos são observados durante o corte, o que torna a usinagem de compósitos um desafio. Este trabalho investiga a usinagem por fresamento do compósito de matriz termoplástica (Toray Cetex® TC910PA6) e do compósito de matriz termorrígida (Toray E732®) utilizando quatro geometrias de ferramentas de corte: duas helicoidais (Hélice neutra com revestimento diamantado (NH) e hélice à esquerda (LH)) e duas geometrias multi-arestas tipo sabugo ( com polimento Zr (ME ZR) e com revestimento diamantado DURA® (ME-D)). Ensaios de fresamento foram realizados variando o avanço por dente “fz” (0,025; 0,050; 0,075 e 0,10 mm/dente) e rotação “n” (4000 e 8000 rpm). A usinabilidade foi avaliada por meio da análise da qualidade superficial, ocorrência de delaminação e danos e monitoramento da influência dos parâmetros de corte na potência consumida, vibração do sistema, emissão acústica e desgaste das ferramentas de corte. Foram aplicadas análises estatísticas de variância (ANOVA), médias (ANOM), sinal-ruído (S/N), testes comparativos e de normalidade, além de otimização utilizando a Metodologia de Superfície de Resposta (RSM). A influência da usinagem nas propriedades mecânicas foi investigada por meio de testes estáticos (tração e flexão) e dinâmicos (fadiga axial). Foi observada maior resistência ao corte para o compósito termorrígido, com grande dependência do fator avanço por dente fz, que levou a maior incidência de ruptura descontínua das fibras favorecendo delaminação tipo II quando aplicados altos fz (0,075 e 0,10 mm/dente). Regiões de porosidade e distribuição descontínua de fibras foram observadas para o compósito termorrígido que podem ter contribuído para alta Ra (2,2 µm). Foi constatado que a redução do avanço por dente pode atuar como fator atenuante no processo de arrancamento das fibras, proporcionando redução na delaminação. O compósito termoplástico apresentou menor incidência de picos vibracionais e menor amplitude de potência consumida, sendo avanço o parâmetro mais influente. Melhoria na qualidade superficial e redução em danos foi observada com a aplicação da ferramenta de hélice à esquerda (LH) associada a fz de 0,025 mm/dente, com Ra de 1,3 µm. O consumo de potência foi criticamente dependente da mudança da geometria da ferramenta de corte. A ferramenta multi-arestas (ME-D) gerou amplitude 4 vezes maiores de potência que as ferramentas helicoidais. Os cavacos coletados apresentaram mudança drástica de forma e tipo com a variação da matriz, tendo a ferramenta (LH) promovido melhor fluxo de escoamento de cavacos, caracterizando como opção ideal para usinagem de acabamento. Foi comprovado que o processo de usinagem de fresamento não reduziu as propriedades mecânicas estáticas dos compósitos, porém, foi observado impacto significativo nas propriedades dinâmicas para a condição fz=0,02 mm/dente e n=4000 rpm, onde a usinagem resultou em delaminação, reduzindo a vida em fadiga para altos níveis de tensão (75 a 85%).
Investigação da usinabilidade no processo de fresamento de compósitos de matriz termoplástica e termorrígida reforçados com fibra de carbono
Keywords: Machining; CFRPs; Statistical Analysis; Mechanical Properties; Usinagem; Plásticos reforçados com fibra de carbono; Resistência de materiais; Ferramentas de corte